Trauma and Transgression in Nature-Based Leisure - Dietsch, Alia M.; Jazi, Everly; Floyd, Myron F.; Ross-Winslow, Danielle; Sexton, Natalie R. (Frontiers in Sports and Active Living, 2021)
The following article contains language, including discussion of racialized trauma, violent oppression, and more, that could trigger strong emotions and other physiological reactions. Our intent is not to retraumatize anyone, but to instead center the voices and experiences of people who have transgressed significant historical trauma and long sought lasting change and equitable outcomes for all.